Pengaruh Profitabilitas, Kepemilikan Manajerial, Komite Audit, dan Audit Tenure terhadap Opini Audit Going Concern - Satrio Rishad Pratama; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to analyze the influence of profitability, managerial ownership, audit committees, and audit tenure on audit opinions going concern. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. Sampling was conducted with purposive sampling technique and the number of samples in this study was 53 companies so that the number of observations of research data obtained was 265. This study was analyzed using logistic regression analysis. The results of the study concluded that profitability and audit committees negatively influenced the opinion of audit going concern, managerial ownership positively influenced the opinion of audit going concern, while audit tenure had no effect on the opinion of audit going concern.